Functionalization-assistant ball milling towards Si/graphene anodes in high performance Li-ion batteries. (30th August 2021) - Zhang, Yin; Cheng, Yangqin; Song, Jinhua; Zhang, Yanjun; Shi, Qian; Wang, Jingxiao; Tian, Fanghua; Yuan, Shuang; Su, Zhou; Zhou, Chao; Wang, Yang; Yang, Sen
Abstract: Due to difficulties with scalability and practical utilization, Si/graphene composites are not yet used as anodes for commercially available lithium-ion batteries. In this paper, we report an accessible and cost-effective ball-milling route to synthesize Si and graphene composites. By introducing amino- and carboxyl-groups, covalent linkage between Si nanoparticles and graphene is created, which solves serious issues of hybrids like poor dispersion and weak connection. This composite features a unique structure, where Si nanoparticles are uniformly attached to the surface or embedded into the inter-layers of the graphene. When used as anodes of lithium-ion batteries, this composite can retain a reversible capacity of 1516.23 mAh g −1 after 100 cycles at 100 mA g −1 . It also exhibited excellent ultra-long-term cycling stability and high rate performance. The electrochemical performance is superior to most reported Si/graphene composites without chemical bonds at the interface, which indicates that covalent bonding can effectively inhibit the irreversible sliding of Si nanoparticles. In addition, EIS measurement had revealed a lower transfer resistance and faster Li-ions diffusion of Si@APTES/ f -Gr, suggesting the integrity of graphene after functionalization. The proposed functionalization-assisted ball-milling approach, therefore, probably enables the large-scale production of Si/Graphene as anodes in high-performance batteries in the future. Graphical abstract: Image 1